What Skills does a GIS Analyst require? - Honfi, Vid; Micsinai R., Péter; Barabás, Tamás (Acta Agraria Kaposváriensis, 2006)
In the University of Kaposvár GIS educating is on since September 2001, primarily for students specialized as economic engineers. The object is to give the graduating students such usable knowledge, that can help them to stand their ground easily in practical life, hereby guaranteeing our institutions good reputation. To reach this it is indispensable to check the quality, modernity of our education permanently and to adapt to the demands of the market. Therefore we have made research, survey of demands with our students possible employers, to find out what knowledge, skills they expect from the employees applying to them. After totalizing the results we got clear image on which points of the education is the change necessary.